(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2025)
The article is devoted to the study of the concept of «family» in the context of traditional Russian values, analysis of the meaning and historical transformations of this term using the methodology of legal hermeneutics. The authors address the problem of meanings and interpretations of the phenomenon of «family», its versatility and variability in historical, philosophical and legal aspects. Traditional values are considered as integral legal and cultural guidelines of modern society. In addition, the article substantiates the relevance and potential of philosophical and legal hermeneutics as a method of interpreting law from the perspective of traditional values. During the study, the following tasks are solved. Firstly, the philosophical origins and legal meanings of the concept of «family» are revealed as the fundamental traditional value. Secondly, the historical development of legal hermeneutics as part of the philosophy of law and the application of key methodological concepts and categories of the hermeneutic method to analyze the value foundations of modern law are explored. Thirdly, an analysis of modern legislation is carried out from the point of view of the lack of a clear definition of the concept of «family» and the need for its research.